Co-Administration of Clomiphene Citrate and Letrozole in Mild Ovarian Stimulation Versus Conventional Controlled Ovarian Stimulation Among POSEIDON Group 4 Patients - Lin, Hsin-Ta; Wu, Meng-Hsing; Tsai, Li-Chung; Chen, Ta-Sheng; Ou, Huang-Tz (Frontiers in Endocrinology, 2022)
This retrospective study assessed the effect of the co-administration of clomiphene citrate (CC) and letrozole in mild ovarian stimulation, compared to conventional regimens, among Patient-Oriented Strategies Encompassing Individualized Oocyte Number (POSEIDON) Group 4 patients. There were 114 POSEIDON Group 4 patients undergoing in vitro fertilization treatments with 216 stimulation cycles recruited from a Taiwan’s reproductive center during 2016-2020. Main outcomes were the numbers, quality of retrieved oocytes and embryo development. Pregnancy outcomes were assessed after embryo transfers. Per stimulation cycle, patients receiving mild stimulation with a combination of CC and letrozole (study group) versus those with COS (control group) had lower numbers of pre-ovulatory follicles (2.00±1.23 vs. 2.37±1.23, p=0.0066) and oocytes retrieved (1.83±1.17 vs. 2.37±1.23, p=0.0017), and lower follicular output rate (58.6% vs. 68.38%, p=0.0093) and mature oocyte output rate (44.29% vs. 52.88%, p=0.0386) but a higher top-quality metaphase II oocyte ratio (66.7% vs. 54.59%, p=0.0444) and a similar fertilization rate (91.67% vs. 89.04%, p=0.4660). With adjustment for significant between-group baseline differences using multivariable logistic generalized estimating equation model analyses, there was no statistical difference in oocytes retrieved and embryo development between the study and control groups, and insignificant increases in successful pregnancies in the study group were found compared to the control group (i.e., odds ratios [95% CIs]: 1.13 [0.55, 232] and 1.50 [0.65, 3.49] for ongoing pregnancy and live birth, respectively). For POSEIDON Group 4 patients, cotreatment of CC and letrozole in mild stimulation may increase the high-quality oocyte ratio and yield comparable fertilization rate and pregnancy outcomes.